Interface coupling modification method for improving binding force of polyether-ether-ketone and surface coating
By performing oxygen plasma treatment, functional modification and chemical modification on polyether ether ketone, the problems of poor surface roughening effect and insufficient interface bonding strength are solved, and efficient metal coating coverage is achieved and strength increase.
Patent Information
- Application Number
- CN202411531430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The extremely high chemical inertia and hydrophobicity of the surface of polyether ether ketone materials leads to poor results in traditional chemical roughening methods, incomplete coating or poor binding force, and the difference in thermal expansion coefficient with the metal layer leads to insufficient interfacial bonding strength.
By subjecting polyether ether ketone to oxygen plasma treatment, functional modification of carboxylated carbon nanofibers and chemical modification of polyimide + polyaromatic sulfone, carboxyl groups, carbonyl groups, sulfanyl groups, and ethers to the polyether ether ketone surface, carboxylate groups, carbonyl groups, sulfanyl groups, and ethers to the polyether ether ketone surface oxygen-containing functional groups such as bonds increase the interfacial bonding strength with the metal layer.
The interface bonding strength between polyether etherketone and the surface plating is significantly improved, the coating is uniform and dense, and the detachment strength of the solder joint is improved, which can withstand hot and cold cycle tests in a wide temperature domain.
Smart Images

Figure CN119463262A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface engineering and relates to an interface coupling modification method for improving the bonding force between polyetheretherketone and a surface coating. Background Art
[0002] Polyetheretherketone (PEEK) is a semi-crystalline aromatic thermoplastic engineering resin. The macromolecular chain contains a large number of rigid benzene rings, flexible ether bonds and carbonyl groups that enhance the intermolecular force, which makes it have many excellent properties, such as excellent high temperature resistance and chemical corrosion resistance, good mechanical properties, radiation resistance, self-lubrication and friction resistance, etc., which makes PEEK materials have broad application prospects in aerospace, electronics and electrical fields. However, because its surface is not conductive, it cannot be used to replace metal materials to achieve functional requirements such as conductivity and welding, and surface metallization treatment is required. Due to the extremely high chemical inertness and hydrophobicity of the surface of PEEK materials, the substrate is first roughened before the metal layer is prepared. When using traditional chromic acid-sulfuric acid solution for chemical roughening, the corrosion of the surface of PEEK materials is uneven, and the roughening time and roughening effect are difficult to grasp, resulting in incomplete coverage of the metal coating or poor bonding. And due to the difference in thermal expansion coefficients between the polyetheretherketone material and the metal layer material, higher requirements are placed on the interface bonding strength between the polyetheretherketone material and the metal layer to meet the thermal stability requirements during application. Therefore, it is necessary to find a surface modification method for the polyetheretherketone material to improve the bonding strength between the polyetheretherketone and the surface coating. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned defects and provide an interface coupling modification method for improving the bonding strength between polyetheretherketone and the surface coating, thereby solving the technical problem that the bonding strength between the existing polyetheretherketone and the surface coating is low. The present invention improves the interface bonding strength between the polyetheretherketone and the surface coating by modifying the polyetheretherketone, and has high flexibility and applicability.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] An interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating, comprising:
[0006] (1) treating polyetheretherketone with oxygen plasma;
[0007] (2) using carboxylated carbon nanofibers to functionalize the surface of polyetheretherketone, so that the surface of polyetheretherketone is connected to the carbon nanofibers through chemical bonds, thereby obtaining carbon nanofiber surface-modified polyetheretherketone;
[0008] (3) Polyetheretherketone is chemically modified by using polyimide and polyarylsulfone to graft oxygen-containing functional groups on the surface of polyetheretherketone to obtain modified polyetheretherketone.
[0009] Furthermore, in step (1), the conditions for oxygen plasma treatment include:
[0010] The power is 300-500W, the atmosphere is oxygen, and the processing time is 5-20min.
[0011] Furthermore, in step (2), the carboxylated carbon nanofibers are obtained by carboxylating helical carbon nanofibers;
[0012] The spiral carbon nanofiber is formed by a plurality of carbon nanowires entangled with each other. The diameter of the spiral carbon nanofiber is 1 to 3 μm, and the length of a single carbon nanowire is 10 to 50 μm.
[0013] Furthermore, in step (2), the method of functionalizing the surface of polyetheretherketone using carboxylated carbon nanofibers comprises:
[0014] The carboxylated carbon nanofibers were uniformly dispersed in deionized water by ultrasonic treatment to obtain a uniform suspension of 0.5 to 1.0 g / L;
[0015] Then the polyetheretherketone is immersed in the suspension for electrophoretic deposition; the conditions of the electrophoretic deposition include: voltage 20-22V, time 8-12min, electrode material is metal plate, and the electrode distance is 60-80mm.
[0016] Furthermore, in step (3), the oxygen-containing functional groups grafted onto the surface of the polyetheretherketone include carboxyl, carbonyl, sulfonyl or ether bonds.
[0017] Furthermore, in step (3), the polyetheretherketone is chemically modified by using a mixed chemical modifier of polyimide and polyarylsulfone;
[0018] In the mixed chemical modifier, the mass fraction of polyimide is 0.5-1.0%, and the mass fraction of polyarylsulfone is 0.5-1.0%.
[0019] Furthermore, in step (3), the conditions for chemical modification treatment include:
[0020] The modification temperature is 30-40°C, the modification time is 1h-2h, and after chemical modification, it is baked in an oven at 80°C-100°C for 8-10h.
[0021] Furthermore, the polyetheretherketone is a plate.
[0022] Furthermore, the modified polyetheretherketone obtained in step (3) is subjected to surface chemical plating after activation treatment;
[0023] After activation treatment, the oxygen-containing functional groups grafted on the surface of the polyetheretherketone are connected to the activated ions through hydrogen bonds, which is used to improve the interface bonding strength between the polyetheretherketone and the coating.
[0024] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0025] (1) The present invention creatively proposes an interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating, wherein the polyetheretherketone is modified to generate oxygen-containing functional groups such as carboxyl, carbonyl, sulfyl, and ether bonds on the surface of the polyetheretherketone, and during the subsequent activation treatment of chemical metal plating, hydrogen bonds are formed with the activated ions, thereby improving the interface bonding strength between the polyetheretherketone and the surface coating;
[0026] (2) The present invention performs interface coupling modification on the surface of polyetheretherketone and then performs chemical nickel plating. The obtained metal layer is uniform and dense, the coating thickness is 5 to 30 μm, the surface resistance is ≤5 mΩ, the coating solder joint tensile strength is ≥7 MPa, and it can withstand -196°C to +120°C hot and cold cycle tests. The metal coating on the surface of polyetheretherketone still maintains good bonding strength in a wide temperature range environment;
[0027] (3) The interface coupling modification method of the present invention can be applied to carbon nanotube, carbon fiber, glass fiber modified polyetheretherketone materials, and has high flexibility and applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The microscopic morphology of polyetheretherketone after oxygen plasma treatment prepared in Example 1 of the present invention;
[0029] Figure 2 The microscopic morphology of the polyetheretherketone after functional modification of the carbon nanofiber prepared in Example 1 of the present invention;
[0030] Figure 3 This is an infrared spectrum test chart of the chemically modified polyetheretherketone prepared in Example 1 of the present invention;
[0031] Figure 4 The test results of the surface contact angle of the polyetheretherketone prepared in Example 1 of the present invention before and after chemical modification; wherein (a) is the test result of the surface contact angle of the polyetheretherketone without interface modification, and (b) is the test result of the surface contact angle of the polyetheretherketone after modification;
[0032] Figure 5 This is a photo of a thermal cycle test after the nickel-plated layer on the surface of polyetheretherketone prepared in Comparative Example 1 of the present invention;
[0033] Figure 6 The microscopic morphology of the polyetheretherketone after functional modification of the carbon nanofibers prepared in Example 2 of the present invention;
[0034] Figure 7 The test results of the surface contact angle of the polyetheretherketone prepared in Example 2 of the present invention before and after chemical modification; wherein (a) is the test result of the surface contact angle of the polyetheretherketone without interface modification, and (b) is the test result of the surface contact angle of the polyetheretherketone after modification;
[0035] Figure 8 This is an infrared spectrum test chart of the chemically modified polyetheretherketone prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0037] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0038] The present invention provides an interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating, wherein the polyetheretherketone is first subjected to oxygen plasma treatment, then subjected to functional modification, and then subjected to chemical modification. The method of the present invention realizes oxygen plasma treatment on the surface of polyetheretherketone, functional modification of carboxyl-wrapped carbon nanofibers, and grafting of oxygen-containing functional groups such as carboxyl, carbonyl, sulfacyl, and ether bonds on the surface of the polyetheretherketone material through polyimide+polyarylsulfone chemical modification treatment, and in the subsequent activation treatment of chemical nickel plating, hydrogen bonding is achieved with the activated ions, thereby improving the interface bonding strength between the polyetheretherketone and the surface coating.
[0039] The present invention discloses an interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating, comprising the following steps:
[0040] (1) treating polyetheretherketone with oxygen plasma to generate oxygen-containing functional groups on the surface of the polyetheretherketone;
[0041] (2) using carboxylated carbon nanofibers to functionalize the surface of polyetheretherketone, so that the surface of polyetheretherketone is connected to the carbon nanofibers through chemical bonds, thereby obtaining carbon nanofiber surface-modified polyetheretherketone;
[0042] (3) Polyetheretherketone is chemically modified by using polyimide + polyarylsulfone, and oxygen-containing functional groups such as carboxyl, carbonyl, sulfyl, and ether bonds are grafted onto the surface. During the subsequent activation treatment of chemical metal plating, hydrogen bonds are formed with the activated ions, thereby ultimately improving the interface bonding strength between polyetheretherketone and the surface coating.
[0043] Furthermore, in step (1), the conditions for oxygen plasma treatment are: power 300-500 W, oxygen atmosphere, and treatment time 5-20 min.
[0044] Furthermore, in step (2), the carboxylated carbon nanofiber is obtained by carboxylating a spiral carbon nanofiber, wherein the spiral carbon nanofiber has a diameter of 1 to 3 μm and is formed by a plurality of carbon nanowires entangled with each other, and a single carbon nanowire has a length of 10 to 50 μm. Functional modification using carboxylated carbon nanofibers can graft carboxyl functional groups on the surface of the material, and utilize the good conductivity and dispersibility of carbon nanofibers to achieve good surface activity of the PEEK surface and improve plating performance.
[0045] Furthermore, in step (2), the functional modification method is: by ultrasonic treatment, the carboxylated carbon nanofibers are uniformly dispersed in deionized water to obtain a uniform suspension of 0.5 to 1.0 g / L, and then the polyetheretherketone is immersed in the carboxylated carbon nanofiber suspension for electrophoretic deposition, the voltage is 20 to 22 V, the time is 8 to 12 min, the electrode material is a metal plate, and the electrode spacing is 60 to 80 mm.
[0046] Furthermore, in step (3), chemical modification is performed using a mixed chemical modifier of polyimide and polyaryl sulfone, the polyimide concentration is 0.5-1.0% (mass fraction), the polyaryl sulfone concentration is 0.5-1.0% (mass fraction), the modification temperature is 30-40°C, the modification time is 1h-2h, and after chemical modification, the mixture is baked in an oven at 80°C-100°C for 8-10h.
[0047] The purpose of using a mixed chemical modifier of polyimide and polyarylsulfone is to provide functional groups such as amide and sulfonyl in the solution. This functional group has certain chemical activity and can also form ether bonds with the molecular chains of PEEK, thereby improving the bonding strength between the PEEK substrate and the metal particles.
[0048] The present invention modifies polyetheretherketone by oxygen plasma treatment, carboxylation of wrapped carbon nanofibers, and polyimide + polyarylsulfone mixed modifiers, so that oxygen-containing functional groups such as carboxyl, carbonyl, sulfacyl, and ether bonds are generated on the surface of polyetheretherketone. When the subsequent activation treatment of chemical metal plating is performed, hydrogen bonds are formed with the activated ions, thereby improving the interface bonding strength between polyetheretherketone and the surface coating. The surface of polyetheretherketone is subjected to interface coupling modification and chemical nickel plating. The obtained metal layer is uniform and dense, the coating thickness is 5 to 30 μm, the surface resistance is ≤5 mΩ, the coating solder joint pull-off strength is ≥7 MPa, and it can withstand -196°C to +120°C hot and cold cycle tests. The metal coating on the surface of polyetheretherketone still maintains good bonding strength in a wide temperature range environment. The interface coupling modification method obtained by the present invention can also be applied to carbon nanotubes, carbon fibers, and glass fiber modified polyetheretherketone materials, and has high flexibility and applicability.
[0049] Example:
[0050] The present invention provides an interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating, comprising the following steps:
[0051] (1) PEEK is treated with oxygen plasma at a power of 300 to 500 W, an oxygen atmosphere, and a treatment time of 5 to 20 min.
[0052] (2) The spiral carbon nanofibers are pickled with a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2 to 3:1, reacted at 70 to 80°C for 6 to 8 hours, and then the carbon nanofibers are dissolved in distilled water and repeatedly filtered to neutrality and then dried to obtain carboxylated spiral carbon nanofibers with high purity. The spiral carbon nanofibers have a diameter of 1 to 3 μm and are formed by multiple carbon nanowires entangled with each other, and the length of a single carbon nanowire is 10 to 50 μm.
[0053] Carboxylated helical carbon nanofibers were used to functionalize polyetheretherketone. The carboxylated helical carbon nanofibers were uniformly dispersed in deionized water by ultrasonic treatment to obtain a uniform suspension of 0.5 to 1.0 g / L. Then, polyetheretherketone was immersed in the suspension of carboxylated helical carbon nanofibers for electrophoretic deposition, wherein the voltage was 20 to 22 V, the time was 8 to 12 min, the electrode material was a metal plate, and the electrode spacing was 60 to 80 mm.
[0054] (3) The polyetheretherketone is chemically modified by using a mixed chemical modifier of 0.5-1.0% (mass fraction) of polyimide and 0.5-1.0% (mass fraction) of polyarylsulfone, the chemical modification temperature is 30-40°C, the chemical modification time is 1h-2h, and after the chemical modification, it is baked in an oven at 80°C-100°C for 8-10h.
[0055] Example 1
[0056] An interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating comprises the following steps:
[0057] First, polyetheretherketone was treated with oxygen plasma at a power of 300 W, an oxygen atmosphere, and a treatment time of 5 min. Figure 1 This is the microstructure of polyetheretherketone after oxygen plasma treatment.
[0058] The spiral carbon nanofibers were pickled with a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.5:1, reacted at 70°C for 6 hours, and then dissolved in distilled water and repeatedly filtered until neutral and dried to obtain carboxylated spiral carbon nanofibers with high purity. The spiral carbon nanofibers have a diameter of 1 μm and are formed by multiple carbon nanowires entangled with each other, and the length of a single carbon nanowire is 10 μm.
[0059] Carboxylated helical carbon nanofibers were used to functionalize polyetheretherketone. The carboxylated helical carbon nanofibers were evenly dispersed in deionized water by ultrasonic treatment to obtain a 0.5 g / L uniform suspension, and then polyetheretherketone was immersed in the carboxylated helical carbon nanofiber suspension for electrophoretic deposition, wherein the voltage was 20 V, the time was 8 min, the electrode material was a metal plate, and the electrode spacing was 60 mm. Figure 2 This is the microstructure of polyetheretherketone after functional modification.
[0060] The activated polyetheretherketone was chemically modified by using a mixed chemical modifier of 0.5% (mass fraction) polyimide and 0.5% (mass fraction) polyarylsulfone, the chemical modification temperature was 30°C, the chemical modification time was 1h, and the chemical modification was baked in an oven at 80°C for 8. Figure 3 This is the infrared spectrum test diagram of polyetheretherketone after chemical modification. The polyetheretherketone after functional modification of carboxylated helical carbon nanofibers has an infrared spectrum of 1739cm -1 The carbonyl (-C=O-) absorption peak appeared at 1628cm -1 A hydroxyl (-OH) peak appeared at 1661 cm-1. The carbonyl peak and the hydroxyl peak group constitute the surface carboxyl group of the functionally modified polyetheretherketone, indicating the formation of a carboxyl functional group. In the infrared spectrum of the chemically modified polyetheretherketone, the carbonyl group is -1 and 1644cm -1 To 1634cm -1Low wavenumber movement (red shift) indicates that the carboxyl functional group (-COOH) on the surface of the modified polyetheretherketone interacts with the vibration frequency of oxygen-containing functional groups such as carbonyl (-C=O-), sulfacyl (O=S=O) and ether bond (-O-) contained in the chemical modifier to form hydrogen bonds, thereby enhancing the interfacial interaction between the chemical modifier and polyetheretherketone. At the same time, due to the action of the chemical modifier, the oxygen-containing functional groups such as -COOH, -C=O-, O=S=O, -O- formed on the surface of polyetheretherketone can also form hydrogen bonds with the activated metal ions before subsequent chemical plating, thereby enhancing the interfacial bonding strength between polyetheretherketone and the surface coating.
[0061] Figure 4 These are the contact angle test results of the polyetheretherketone surface before and after chemical modification, indicating that the polyetheretherketone surface has good wettability after chemical modification.
[0062] The chemically modified polyetheretherketone was subjected to chemical roughening, sensitization, activation, and chemical nickel plating in order to test the bonding strength between polyetheretherketone and the metal coating. The roughening solution includes the following components: 110g / L chromic acid, 220mL sulfuric acid, 100g / L phosphoric acid, and 20g / L manganese dioxide. The roughening temperature is 75°C and the roughening time is 8min. After roughening, it is fully cleaned to prevent chromium ions or excess sulfuric acid from being brought to the next process to contaminate the solution, reduce the solution life, and reduce the sensitization effect. After roughening, stannous chloride solution and palladium chloride solution are used for sensitization and activation treatment respectively, and then chemical nickel plating is carried out. The chemical nickel plating adopts a medium phosphorus nickel solution, and the chemical nickel plating solution includes 12g / L basic nickel carbonate, 22g / L sodium hypophosphite, 18mg / L citric acid, 3g / L succinic acid, 10g / L ammonium bifluoride, 1.5mL / L saccharin sodium, 12mL / L hydrofluoric acid (40%), 22mL / L ammonia water, and 0.8mL / L stabilizer. The nickel plating temperature is 78°C, and the nickel layer is a chemical nickel-phosphorus alloy. When chemical nickel plating, a pump circulation stirring and a flow equalizing plate should be set in the plating tank to make the plating solution flow evenly during plating. The thickness of the coating is 8-10μm, and the surface resistance of the coating is measured by a surface resistance tester to be 4mΩ.
[0063] Through the solder joint pull-off strength test of the chemical nickel plating layer on the surface of polyetheretherketone, the solder joint bonding strength of the chemical nickel plating layer of polyetheretherketone was measured to be 7MPa. Compared with the interface without coupling modification (3.5MPa), the interface bonding strength between polyetheretherketone and the metal layer was significantly improved. The thermal cycle test was conducted, and the test piece was placed in a 120℃ oven, baked at high temperature for 10 minutes, and then quickly taken out and placed in liquid nitrogen for 10 minutes. After the hot and cold cycle test, the metal layer on the surface of polyetheretherketone had no bulging, cracking, etc., and the coating had good bonding strength ( Figure 5 ).
[0064] Example 2
[0065] An interface coupling modification method for improving the bonding strength between polyetheretherketone and a surface coating comprises the following steps:
[0066] First, polyetheretherketone was treated with oxygen plasma at a power of 400 W, an oxygen atmosphere, and a treatment time of 20 min.
[0067] The spiral carbon nanofibers were acid-washed with a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, reacted at 70°C for 6 hours, and then dissolved in distilled water and repeatedly filtered until neutral and dried to obtain carboxylated spiral carbon nanofibers with high purity. The spiral carbon nanofibers have a diameter of 5 μm and are formed by multiple carbon nanowires entangled with each other, and the length of a single carbon nanowire is 20 μm.
[0068] Carboxylated helical carbon nanofibers were used to functionalize polyetheretherketone. The carboxylated helical carbon nanofibers were evenly dispersed in deionized water by ultrasonic treatment to obtain a 1.0 g / L uniform suspension, and then polyetheretherketone was immersed in the carboxylated helical carbon nanofiber suspension for electrophoretic deposition, wherein the voltage was 22 V, the time was 10 min, the electrode material was a metal plate, and the electrode spacing was 80 mm. Figure 6 This is the microstructure of polyetheretherketone after functional modification of carbon nanofibers.
[0069] Chemical modification of polyetheretherketone: Polyetheretherketone was chemically modified by using a mixed chemical modifier of 1.0% (mass fraction) polyimide and 1.0% (mass fraction) polyarylsulfone, the chemical modification temperature was 40°C, the chemical modification time was 2h, and after chemical modification, it was baked in an oven at 100°C for 10h. Figure 7 This is the contact angle test result of the chemically modified polyetheretherketone surface, which shows that the chemically modified polyetheretherketone surface has good wettability.
[0070] Figure 8 This is the infrared spectrum test diagram of polyetheretherketone after chemical modification. The polyetheretherketone after functional modification of carboxylated helical carbon nanofibers has an infrared spectrum of 1739cm -1 The carbonyl (-C=O-) absorption peak appeared at 1628cm -1 The hydroxyl (-OH) peak appeared at 1661 cm-1, and the carbonyl peak and hydroxyl peak groups constituted the surface carboxyl groups of polyetheretherketone after functionalization and activation, indicating the formation of carboxyl functional groups. In the infrared spectrum of chemically modified polyetheretherketone, the carbonyl group was -1 and 1644cm -1 To 1633cm -1Low wavenumber movement (red shift) indicates that the carboxyl functional group (-COOH) on the surface of polyetheretherketone interacts with the vibration frequency of oxygen-containing functional groups such as carbonyl (-C=O-), sulfacyl (O=S=O) and ether bond (-O-) contained in the chemical modifier to form hydrogen bonds, thereby enhancing the interfacial interaction between the chemical modifier and polyetheretherketone. At the same time, due to the action of the chemical modifier, the oxygen-containing functional groups such as -COOH, -C=O-, O=S=O, -O- formed on the surface of polyetheretherketone can also form hydrogen bonds with the activated metal ions before subsequent chemical plating, thereby enhancing the interfacial bonding strength between polyetheretherketone and the surface coating.
[0071] The chemically modified polyetheretherketone was subjected to chemical roughening, sensitization, activation, and chemical nickel plating in order to test the bonding strength between polyetheretherketone and the metal coating. The roughening solution includes the following components: 110g / L chromic acid, 220mL sulfuric acid, 100g / L phosphoric acid, and 20g / L manganese dioxide. The roughening temperature is 75°C and the roughening time is 8min. After roughening, it is fully cleaned to prevent chromium ions or excess sulfuric acid from being brought to the next process to contaminate the solution, reduce the solution life, and reduce the sensitization effect. After roughening, stannous chloride solution and palladium chloride solution are used for sensitization and activation treatment respectively, and then chemical nickel plating is carried out. The chemical nickel plating adopts medium phosphorus nickel solution, and the chemical nickel plating solution includes 12g / L basic nickel carbonate, 22g / L sodium hypophosphite, 18mg / L citric acid, 3g / L succinic acid, 10g / L ammonium bifluoride, 1.5mL / L saccharin sodium, 12mL / L hydrofluoric acid (40%), 22mL / L ammonia water, and 0.8mL / L stabilizer. The nickel plating temperature is 78°C, and the nickel layer is a chemical nickel-phosphorus alloy. When chemical nickel plating, a pump circulation stirring and a flow equalizing plate should be set in the plating tank to make the plating solution flow evenly during plating. The coating thickness is 20μm, and the surface resistance of the coating is measured by a surface resistance tester to be 2mΩ.
[0072] The tensile strength of the solder joints of the chemical nickel-plated layer on the surface of polyetheretherketone was tested, and the solder joint bonding strength of the chemical nickel-plated layer of polyetheretherketone was measured to be 8.9MPa. Compared with the interface coupling modification without modification (3.5MPa), the interface bonding strength between polyetheretherketone and the metal layer was significantly improved. The thermal cycle test was conducted, and the test piece was placed in a 120℃ oven, baked at high temperature for 10 minutes, and then quickly taken out and placed in liquid nitrogen for 10 minutes. After the hot and cold cycle test, the metal layer on the surface of polyetheretherketone had no bulging, cracking, etc., and the coating had good bonding strength.
[0073] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0074] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. An interface coupling modification method for improving the bonding strength between polyetheretherketone and surface coating, characterized in that: include: (1) treating polyetheretherketone with oxygen plasma; (2) using carboxylated carbon nanofibers to functionalize the surface of polyetheretherketone, so that the surface of polyetheretherketone is connected to the carbon nanofibers through chemical bonds, thereby obtaining carbon nanofiber surface-modified polyetheretherketone; (3) Polyetheretherketone is chemically modified by using polyimide and polyarylsulfone to graft oxygen-containing functional groups on the surface of polyetheretherketone to obtain modified polyetheretherketone.
2. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (1), the conditions for oxygen plasma treatment include: The power is 300-500W, the atmosphere is oxygen, and the processing time is 5-20min.
3. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (2), the carboxylated carbon nanofibers are obtained by carboxylating helical carbon nanofibers; The spiral carbon nanofiber is formed by a plurality of carbon nanowires entangled with each other. The diameter of the spiral carbon nanofiber is 1 to 3 μm, and the length of a single carbon nanowire is 10 to 50 μm.
4. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (2), the method of functionalizing the surface of polyetheretherketone using carboxylated carbon nanofibers comprises: The carboxylated carbon nanofibers were uniformly dispersed in deionized water by ultrasonic treatment to obtain a uniform suspension of 0.5 to 1.0 g / L; Then the polyetheretherketone is immersed in the suspension for electrophoretic deposition; the conditions of the electrophoretic deposition include: voltage 20-22V, time 8-12min, electrode material is metal plate, and the electrode distance is 60-80mm.
5. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (3), the oxygen-containing functional groups grafted onto the surface of the polyetheretherketone include carboxyl, carbonyl, sulfonyl or ether bond.
6. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (3), polyetheretherketone is chemically modified by using a mixed chemical modifier of polyimide and polyarylsulfone; In the mixed chemical modifier, the mass fraction of polyimide is 0.5-1.0%, and the mass fraction of polyarylsulfone is 0.5-1.0%.
7. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: In step (3), the conditions for chemical modification treatment include: The modification temperature is 30-40°C, the modification time is 1h-2h, and after chemical modification, it is baked in an oven at 80°C-100°C for 8-10h.
8. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: Polyetheretherketone is a sheet material.
9. The method for improving the interfacial coupling modification of polyetheretherketone and the surface coating according to claim 1, characterized in that: The modified polyetheretherketone obtained in step (3) is subjected to surface chemical plating after activation treatment; After activation treatment, the oxygen-containing functional groups grafted on the surface of the polyetheretherketone are connected to the activated ions through hydrogen bonds, which is used to improve the interface bonding strength between the polyetheretherketone and the coating.